THE EFFECTIVENESS OF LUNG TUBERCULOSIS EDUCATIONAL VIDEO TO INCREASE KNOWLEDGE AND ATTITUDES OF MASKS USE IN FAMILIES LIVING WITH TUBERCULOSIS PATIENTS - Yati Sri Hayati; Venty Aprilia Putri; Mifetika Lukitasari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
Lung tuberculosis is still a government concern as an infectious disease that causesdeath. The prevalence of lung tuberculosis is still increasing, one of the causes is the highrate of transmission. Families caring for lung tuberculosis patients have a higher risk oftransmitted because of the high intensity of interactions. Families must understand andbe aware of how lung tuberculosis is transmitted and how to prevents it. The researchobjective was to determine the effectiveness of education through video regarding lungtuberculosis transmission towards increasing knowledge and attitudes in using masks infamilies with lung tuberculosis patients. The research design was pre-experimental withone group pre-post test design. The instrument used was a questionnaire to measureknowledge and attitudes, and an educational video with a duration of 15 minutes.Respondents in this study are one of the family members who are the main responsiblefor tuberculosis patients, totaling 23 people. The results showed the mean pre-testfor knowledge was 71.00 ± 8,954 and attitudes were 21.65 ± 4.074. Meanwhile, afterproviding education, the results showed the mean of knowledge is 94.70 ± 6.931 and theattitude is 25.96 ± 3140. There was a significant effect of providing lung tuberculosistransmission educational videos on increasing knowledge and attitudes in using masksin families with lung tuberculosis patients. The use of educational video media canbe better developed as an alternative strategy in efforts to prevent lung tuberculosistransmission, both in hospitals and in the community